Beispiel Nr: 03
$ \text{Gegeben:} \\ \text{Vektoren: } \vec{A} =\left( \begin{array}{c} a_1 \\ a_2 \\ a_3 \\ \end{array} \right) \quad \vec{B} =\left( \begin{array}{c} b_1 \\ b_2 \\ b_3 \\ \end{array} \right) \\ \\ \text{Gesucht:} \\ \text{Länge der Vektoren:} \\ \text{Fläche des Parallelogramms} \\ \text{Vektorprodukt} \\ \text{Skalarprodukt} \\ \text{Lineare Abhängigkeit von 2 Vektoren}\\ \\ \\ \textbf{Gegeben:} \\ \text{Vektor: } \vec{A} =\left( \begin{array}{c} 2 \\ 6 \\ 4 \\ \end{array} \right) \quad \vec{B} =\left( \begin{array}{c} -8 \\ -1 \\ -3 \\ \end{array} \right) \\ \\ \\ \textbf{Rechnung:} \\ \text{Vektoren: } \vec{a} =\left( \begin{array}{c} 2 \\ 6 \\ 4 \\ \end{array} \right) \quad \vec{b} =\left( \begin{array}{c} -8 \\ -1 \\ -3 \\ \end{array} \right) \\ \bullet \text{Länge der Vektoren:} \\ \left|\vec{a}\right| =\sqrt{a_1^2+a_2^2+a_3^2} \\ \left|\vec{a}\right| =\sqrt{2^2+6^2+4^2} \\ \left|\vec{a}\right| =7,48 \\ \left|\vec{b}\right| =\sqrt{b_1^2+b_2^2+b_3^2} \\ \left|\vec{b}\right| =\sqrt{\left(-8\right)^2+\left(-1\right)^2+\left(-3\right)^2} \\ \quad \left|\vec{b}\right| =8,6 \\ \bullet \text{Skalarprodukt:} \\ \vec{a} \circ \vec{b}=2 \cdot -8 + 6 \cdot -1 +4 \cdot -3 = -34 \\ \bullet \text{Vektorprodukt:} \\ \vec{a} \times \vec{b}= \left( \begin{array}{c} 6 \cdot\left(-3\right)-4\cdot\left(-1\right) \\ 4\cdot\left(-8\right)-\left(-3\right)\cdot2 \\ 2\cdot\left(-1\right)-6\cdot\left(-8\right) \\ \end{array} \right) \\ \vec{c} = \vec{a} \times \vec{b}= \left( \begin{array}{c} -14 \\ -26 \\ 46 \\ \end{array} \right) \\ \bullet \text{Fläche des Parallelogramms} \\ \left|\vec{c}\right| =\sqrt{\left(-14\right)^2+\left(-26\right)^2+46^2} \\ \left|\vec{c}\right| =54,7 \\ \bullet \text{Schnittwinkel:} \\ \cos \alpha= \displaystyle\frac{ \vec{a} \circ \vec{b}}{ \left|\vec{a}\right| \cdot \left|\vec{b}\right|}\\ \cos \alpha= \left|\displaystyle\frac{-34}{7,48 \cdot 8,6} \right| \\ \cos \alpha= \left| -0,528 \right| \\ \alpha=58,1 \\ \bullet \text{Lineare Abhängigkeit von 2 Vektoren}\\ \left( \begin{array}{c} 2 \\ 6 \\ 4 \\ \end{array} \right) =k \cdot \left( \begin{array}{c} -8 \\ -1 \\ -3 \\ \end{array} \right) \\ \begin{array}{cccc} 2&=&-8 k & \quad /:-8 \quad \Rightarrow k=-\frac{1}{4} \\ 6&=&-1 k & \quad /:-1 \quad \Rightarrow k=-6 \\ 4&=&-3 k & \quad /:-3 \quad \Rightarrow k=-1\frac{1}{3} \\ \end{array} \\ \\ \Rightarrow \text{Vektoren sind linear unabhängig - nicht parallel} \\ $